2020
DOI: 10.1007/s11356-020-10453-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of European and hybrid aspen clones efficiency based on height growth and removal percentage of petroleum hydrocarbons—a field trial

Abstract: Soils polluted by organic or inorganic pollutants are an emerging global environmental issue due to their toxic effects. A phytoremediation experiment was conducted to evaluate the extraction potential of three European aspen clones (R2, R3, and R4) and seven hybrid aspen clones (14, 27, 34, 134, 172, 191, and 291) grown in soils polluted with hydrocarbons (includes polycyclic aromatic hydrocarbons (PAH) and total petroleum hydrocarbons (TPH)). Height growth, plant survival rates, and .hydrocarbon removal effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Compared to the other clones, hybrid aspen clone 291 had a higher survival rate in diesel-contaminated soil ( Figure 2 a). These results are consistent with the findings of Salam et al [ 37 ], who reported the survival of European aspen and hybrid aspen clones grown in hydrocarbons-contaminated soils. In diesel-contaminated soil, European aspen clone R4 survived more effectively than R3 ( Figure 2 a).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Compared to the other clones, hybrid aspen clone 291 had a higher survival rate in diesel-contaminated soil ( Figure 2 a). These results are consistent with the findings of Salam et al [ 37 ], who reported the survival of European aspen and hybrid aspen clones grown in hydrocarbons-contaminated soils. In diesel-contaminated soil, European aspen clone R4 survived more effectively than R3 ( Figure 2 a).…”
Section: Discussionsupporting
confidence: 93%
“…This would suggest that European aspen and hybrid aspen clones have considerable potential for phytoremediation experiments since European aspen and hybrid aspen clones showed a 76% survival rate in this study. A field trial demonstrated that European aspen and hybrid aspen clones could survive in hydrocarbons-contaminated soil with a 59–64% survival rate [ 37 ]. Compared to the other clones, hybrid aspen clone 291 had a higher survival rate in diesel-contaminated soil ( Figure 2 a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations